Kekerasan Berbasis Gender Dalam Politik Digital: Analisis Kasus Serangan Terhadap Politisi Perempuan Di Media Sosial - Diah Setiani; Assyifa Aulia Chandra; Ika Arinia Indriyany (CV. ITTC INDONESIA, 2026)
The development of social media has opened up broader opportunities for political participation, including for women, but has also posed a risk of online gender-based violence (OGBV). This study analyzes patterns of violence against female politicians on social media through Kate Manne's misogyny perspective, emphasizing the social function of misogyny as a mechanism for surveillance and enforcement of patriarchal norms. A desk study method was used to examine literature, news stories, and reports from relevant organizations, with content analysis aimed at identifying patterns and themes of violence. The results show that female politicians often face behavioral surveillance, punishment for perceived deviant behavior, and delegitimization of leadership through misogynistic comments, verbal abuse, threats, and the dissemination of negative content. These attacks not only target gender identity but also serve to uphold male dominance in politics. These findings confirm that digital spaces, while offering opportunities for representation, continue to foster patriarchal structures and create additional social pressures for women in politics. This research provides important insights into the mechanisms of misogyny in the digital realm and its implications for women's participation in Indonesian democracy and politics.